Питання нормативно-правового регулювання діяльності Президента України - Ковальчук, Олена; Kovalchuk, Olena (Видавництво Львівської політехніки, 2023)
У статті розглянуто питання нормативно-правового регулювання діяльності Президента України, зокрема, визначення повноважень Президента України в Конституції України та проблем нормативно-правового регулювання реалізації повноважень Президента України на законодавчому рівні. Пропонується прийняття Закону України «Про Президента України», до положень якого включити питання: повноважень Президента України, гарантій його діяльності, особливостей повноважень Президента України у відносинах з Верховною Радою України, Кабінетом Міністрів України та іншими органами влади і їх посадовими особами, актів Президента України, строків виконання повноважень Президентом України, припинення повноважень Президента України, гарантій безпеки Президента України та членів його сім'ї, матеріально-побутового забезпечення Президента України, створення та функціонування консультативних, дорадчих та інших допоміжних органів і служб при Президенті України та інші. Вбачається, що особливе місце у зазначеному законі повинно бути визначено для процедурних питань реалізації повноважень Президента України, з метою уникнення в процесі їх виконання двоякого трактування способу їх здійснення.

The article examines the issue of normative and legal regulation of the activities of the President of Ukraine, in particular, the definition of the powers of the President of Ukraine in the Constitution of Ukraine and the problems of normative and legal regulation of the implementation of the powers of the President of Ukraine at the legislative level. It is proposed to adopt the Law of Ukraine "On the President of Ukraine", the provisions of which include the following issues: powers of the President of Ukraine, guarantees of his activities, features of the powers of the President of Ukraine in relations with the Verkhovna Rada of Ukraine, the Cabinet of Ministers of Ukraine and other authorities and their officials, acts of the President of Ukraine , the term of office of the President of Ukraine, the termination of the powers of the President of Ukraine, security guarantees of the President of Ukraine and his family members, the material support of the President of Ukraine, the creation and functioning of advisory, advisory and other auxiliary bodies and services under the President of Ukraine, and others. It is considered that a special place in the mentioned law should be defined for procedural issues of exercising the powers of the President of Ukraine, in order to avoid a double interpretation of the way of their implementation in the process of their implementation.
The issue of regulatory and legal regulation of the activities of the President of Ukraine
Keywords: Президент України; акти Президента України; закон; повноваження; припинення повноважень; діяльність; President of Ukraine; acts of the President of Ukraine; law; powers; termination of powers; activity; 342.511